Bilateral gluteal advancement flap for treatment of recurrent sacrococcygeal pilonidal disease: A prospective cohort study. (May 2016) - Elalfy, Khaled; Emile, Sameh; Lotfy, Ahmed; Youssef, Mohamed; Elfeki, Hossam
Abstract: Background: There is controversy about the best surgical approach for recurrent pilonidal disease (PND) up till now. This study aims to evaluate the efficacy of bilateral gluteal fascio-myo-cutaneous advancement flap (BGFMCF) in treatment of recurrent PND. Patient and methods: Forty patients (35 males, 5 females) with recurrent PND were admitted and treated with BGFMCF. Variables assessed were incidence of recurrence, postoperative complications, patients' satisfaction and quality of life. Results: Patients had a mean age of 25 ± 6.8 years and a mean body mass index of 28.4 ± 2.7. Mean operative time was 87 ± 13 min and mean length of hospital stay was 3 ± 0.7 days. Mean period of follow-up was 15.8 ± 4.9 months. Recurrence was detected in 2 (5%) patients and minor complications occurred in 6 (15%) patients. Thirty eight (95%) patients were satisfied by the procedure at the end of follow-up period. Conclusion: BGFMCF is an effective procedure for treatment of recurrent sacrococcygeal PND with low recurrence rate and acceptable morbidity. Highlights: 40 patients with recurrent PND were treated with bilateral gluteal advancement flap. Patients had a mean age of 25.1 ± 6.8 years and mean BMI of 28.4 ± 2.7. Mean operative time was 87 ± 13 min. Mean LOS was 3 ± 0.72 days. Recurrence occurred in 2 patients and minor complications in 6 patients. 38 patients were satisfied by the end of follow-up period.